HEALTH PROMOTION ANIMATION ABOUT BUYING SNACKS CARELESSLY PROTECTION FOR STUDENT OF SDN BANJARWATI LAMONGAN - nashrur razzaq (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2018)
Malicious snack behavior has been still often done by children. Lack of information about healthy snacks to be one of the causes of it. For that need the promotion of health with the aim of increasing the knowledge of children. The media used to determine the success of delivering information on students SDN Banjarwati Lamongan. This research was conducted with a research and development (R & D) design that aims to develop film media for health promotion. This study uses questionnaires given to 50 students. And interviews that aim to explore the characteristics of the target. In addition, expert reviews are also conducted to get suggestions on prototype and animation media that have been developed. Students of SDN Banjarwati require the addition of information about the content of dye and hygiene presentation of healthy snacks. Animation made tailored to the characteristics of students who love animation with the genre of adventure and use the Indonesian language. Movie media duration of 3 minutes with meticulous messages before consumption, using a rational approach with the aim of target groups who watch animation will gain new knowledge